ANALISIS PENGUKURAN KINERJA DAN PERENCANAAN STRATEGI MENGGUNAKAN PENDEKATAN BALANCED SCORECARD DAN HOSHIN KANRI: STUDI KASUS DI PERUSAHAAN TEKSTIL - Sandrina, Laura; Kosasih, Wilson; Salomon, Lithrone Laricha (Jurnal Mitra Teknik Industri, 2023)
This research was conducted in manufacturing company that focuses on the textile sector, especially raw materials for making woven labels. In calculating the company's current performance, what is considered in outline is the financial aspect, so that other aspects have not been considered. Intense competition in the current market share will certainly make the company's condition decline. Therefore it is necessary to have performance measurement and strategic planning. This performance calculating uses the Balanced Scorecard method which obtains 12 Key Performance Indicators (KPI), then calculated using the Objective Matrix and the Traffic Light System. The results of the Balanced Scorecard are: Financial Perspective 0.428, Customer Perspective 0.332, Internal Business Process Perspective 0.119, Learning and Growth Perspective 0.121. The results of the assessment using the Objective Matrix and Traffic Light System showed that 5 indicators were good, 2 performance indicators were not optimal, and 5 performance indicators needed improvement. Then proceed to strategic planning using the Hoshin Kanri method with the X-Matrix.